Evolution of electric communication signals in the South American ghost knifefishes (Gymnotiformes: Apteronotidae): A phylogenetic comparative study using a sequence-based phylogeny. Issue 3 (October 2016) - Smith, Adam R.; Proffitt, Melissa R.; Ho, Winnie W.; Mullaney, Claire B.; Maldonado-Ocampo, Javier A.; Lovejoy, Nathan R.; Alves-Gomes, José A.; Smith, G. Troy
Highlights: We constructed a robust sequence-based phylogenetic tree of Apteronotidae. We provide the first description of electrocommunication signals in two apteronotid species. Ancestral state reconstructions demonstrate rapid evolution of signal parameters. Abstract: The electric communication signals of weakly electric ghost knifefishes (Gymnotiformes: Apteronotidae) provide a valuable model system for understanding the evolution and physiology of behavior. Apteronotids produce continuous wave-type electric organ discharges (EODs) that are used for electrolocation and communication. The frequency and waveform of EODs, as well as the structure of transient EOD modulations (chirps), vary substantially across species. Understanding how these signals have evolved, however, has been hampered by the lack of a well-supported phylogeny for this family. We constructed a molecular phylogeny for the Apteronotidae by using sequence data from three genes (cytochrome c oxidase subunit 1, recombination activating gene 2, and cytochrome oxidase B) in 32 species representing 13 apteronotid genera. This phylogeny and an extensive database of apteronotid signals allowed us to examine signal evolution by using ancestral state reconstruction (ASR) and phylogenetic generalized least squares (PGLS) models. Our molecular phylogeny largely agrees with another recent sequence-based phylogeny and identified five robust apteronotid clades: (i) Sternarchorhamphus   +   Orthosternarchus, (ii) Adontosternarchus, (iii) Apteronotus  +  Parapteronotus, (iv) Sternarchorhynchus, and (v) a large clade including Porotergus, 'Apteronotus', Compsaraia, Sternarchogiton, Sternarchella, and Magosternarchus . We analyzed novel chirp recordings from two apteronotid species ( Orthosternarchus tamandua and Sternarchorhynchus mormyrus ), and combined data from these species with that from previously recorded species in our phylogenetic analyses. Some signal parameters in O. tamandua were plesiomorphic (e.g., low frequency EODs and chirps with little frequency modulation that nevertheless interrupt the EOD), suggesting that ultra-high frequency EODs and "big" chirps evolved after apteronotids diverged from other gymnotiforms. In contrast to previous studies, our PGLS analyses using the new phylogeny indicated the presence of phylogenetic signals in the relationships between some EOD and chirp parameters. The ASR demonstrated that most EOD and chirp parameters are evolutionarily labile and have often diversified even among closely related species.